META-ANALYSIS: THE EFFECTIVENESS OF DIGITAL TECHNOLOGY IN BIOLOGY LEARNING IN INDONESIA - Alya Bestari; Lusi Trika Wati; Rani Rahim; Sri Wulandari; Dodi Dwi Risaundi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
The development of digital technology has made a significant contribution to the transformation of biology learning in Indonesia. This study aims to analyze the effectiveness of using digital technology on learning outcomes of senior high school students. The method used is a meta-analysis of 20 relevant research articles published between 2020 and 2025. The data analyzed consists of average learning outcomes of experimental and control classes, which were then calculated using effect size. The results indicate that digital technology is generally effective in improving biology learning outcomes across all senior high school levels, with a higher tendency of effectiveness in upper-level classes. Furthermore, the type of digital technology-based media also influences the level of effectiveness, where interactive, visual, and immersive media such as artificial intelligence, audiovisuals, and virtual laboratories have a greater impact compared to less interactive media. Therefore, the utilization of digital technology in biology learning needs to be adjusted to the characteristics of the material and students, and supported by teacher competence to ensure optimal learning.